CONTEMPORARY ENGINEERING EDUCATION: UNITY IN DIVERSITY - Vasiliy G. Ivanov; Julia N. Ziyatdinova; Phillip A. Sanger (Moscow Polytechnic University, 2016)
The paper describes new trends in global engineering education from the view of professional and social cultural diversity. Different approaches to diversity in engineering are analyzed, the importance of personal and professional life experiences for creativity in engineering is stressed, recommendations for engineering team formation are given. The ideas on diversity in engineering education discussed at the 122nd Annual Conference of American Society for Engineering education in Seattle, USA on June 14-17, 2015 are presented, including the reports given at one of the three International Forum plenaries on engineering education in Russia, its traditions and prospects.